2008
DOI: 10.1177/0954008308095288
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Poly(ether imide) Membranes via Surface-Initiated Atom-Transfer Radical Polymerization and their Use in Antifouling

Abstract: Poly(ether imide) (PEI) was chloromethylated by a simple one-step method under mild conditions to provide surface benzyl chloride groups as the active initiators for the surface-initiated atomtransfer radical polymerization (ATRP). Functional hydrophilic polymer brushes of poly(ethylene glycol) monomethacrylate and sodium 4-styrenesulfonate, as well as their block copolymer brushes, were synthesized via surface-initiated ATRP from the chloromethylated PEI membrane surfaces. The surfacemodified membranes were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Among several approaches, atom-transfer radical polymerization (ATRP) has proven to be a valid tool for initiating polymerization for a wide range of monomers and even water can be used as the solvent for ATRP [23,24]. There are several studies on ATRP to fabricate hydrophilic and antifouling membranes [25][26][27]. For example, Chiang et al [27] grafted sulfobetaine methacrylate (SBMA) on the surface of poly(vinylidene fluoride) (PVDF) membrane with the ATRP method, and found that hardly any bovine serum albumin (BSA) adsorption was observed and the adsorption of c-globulin was also greatly reduced after SBMA grafting.…”
Section: Introductionmentioning
confidence: 99%
“…Among several approaches, atom-transfer radical polymerization (ATRP) has proven to be a valid tool for initiating polymerization for a wide range of monomers and even water can be used as the solvent for ATRP [23,24]. There are several studies on ATRP to fabricate hydrophilic and antifouling membranes [25][26][27]. For example, Chiang et al [27] grafted sulfobetaine methacrylate (SBMA) on the surface of poly(vinylidene fluoride) (PVDF) membrane with the ATRP method, and found that hardly any bovine serum albumin (BSA) adsorption was observed and the adsorption of c-globulin was also greatly reduced after SBMA grafting.…”
Section: Introductionmentioning
confidence: 99%
“…A few examples include self-assembled monolayer of thiols on gold, chlorosilanes on silicon oxide surfaces, and alkyl cations through ion exchange on mica and montmorillonite . Surface functional groups of polymeric materials such as cellulose, chitosan, poly(ether imide), and graphene oxide have also been chemically modified to introduce ATRP initiators. Recently, aryldiazonium-based compounds have been successfully employed to introduce initiators on conducting substrates such as metals and glassy carbon (GC) through an electrochemical approach.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(ether imide) (PEI) was chloromethylated with the paraformaldehyde/ Me 3 SiCl/SnCl 4 system in chloroform at 50 • C and for 24 h [91]. The degree of chloromethylation, estimated as the number of chloromethyl groups per repeat unit of PEI, was about 0.22.…”
Section: Paraformaldehyde/me 3 Six a Halomethylating Agentmentioning
confidence: 99%